Biological control of soybean charcoal rot by native Trichoderma koningiopsis in Tucumán, Argentina - Bleckwedel, Juliana (2024)
Macrophomina phaseolina (Tassi) Goid. (Mp) is the causal agent of charcoal rot in soybean, an economically serious and potentially destructive disease. Chemical control sometimes has limited effects on disease severity and may pose a threat to the environment, so the use of Trichoderma as a biological product could be a feasible alternative for charcoal rot management. The objective of this research was to isolate and characterize native Trichoderma spp. from northwestern Argentina and study their antagonistic effect against Mp in soybean. Isolations were performed from soil samples followed by cultural and microbiological characterization of the Trichoderma spp. isolates collected. Then, the antagonist effect against Mp was studied in vitro, under greenhouse conditions, and finally under field conditions with pathogen artificial inoculations during two soybean crop seasons (2020 and 2021). The results demonstrated that isolate Tr009 had a biocontrol effect against Mp in soybean. This control was evidenced in vitro and under controlled and field conditions with high emergency of plants compared to the Mp inoculated control. Under field conditions, treatments that included Trichoderma presented lower disease severity, colony-forming unit index and disease severity index values than the pathogen inoculated control. Moreover, Tr009 improved weight and length of soybean plants under greenhouse conditions. Isolate Tr009 was identified as Trichoderma koningiopsis by molecular methods. These results indicate that this biological tool can be used against Mp and thus favor a sustainable management of soybean charcoal rot.